Differences in inter-segment coordination between high- and low-calibre ice hockey players during forward skating - Mazurek, C. M.; Pearsall, D. J.; Renaud, P. J.; Robbins, S.M. (Sports Biomechanics, 2023)
The objective was to compare lower extremity inter-segment coordination between high-calibre and low-calibre ice hockey players during forward full stride skating. A 10-camera Vicon motion capture system collected kinematic data on male high-calibre (n = 8) and low-calibre (n = 8) participants. Continuous relative phase (CRP) was calculated for shank-sagittal/thigh-sagittal, shank-sagittal/thigh-frontal and foot-sagittal/shank-sagittal segment pairs. Principal component analysis (PCA) was used to extract features of greatest variability of the CRP and hierarchical linear model investigated relationships between principal components and skill level. High-calibre players demonstrated more out-of-phase coordination (higher CRP) of shank-sagittal/thigh-sagittal throughout glide/push-off (p = 0.011) as well as a delay in the transition to more in-phase coordination during early recovery phase (p = 0.014). For shank-sagittal/thigh-frontal (p = 0.013), high-calibre players had more out-of-phase coordination throughout the entire stride. High-calibre players were also associated with an earlier transition to more out-of-phase coordination of the foot-sagittal/shank-sagittal during push-off (p = 0.007) and a smaller difference in CRP between mid-glide/early recovery (p = 0.016). Utilising more out-of-phase modes of coordination may allow players to more easily adjust to optimal modes of coordination throughout skating strides. Skating drills incorporating varying speed, directionality and external stimuli may encourage the development of more optimal coordination during skating.